1998
DOI: 10.2169/internalmedicine.37.18
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Understanding and Opinion about Informed Consent for Coronary Angiography in a Rural Japanese Hospital.

Abstract: Based on an anonymous questionnaire obtained from 102 Japanese in-patients at a rural Japanese hospital whounderwent coronary angiography, the patients understanding of information about the procedure, their perception of consent and their attitude toward it were investigated. Thepatients were able to recall 63.8 %of the contents of the information. There wasa statistically significant correlation between the patients' educational status and the recall test score of the information. Older (65 years old and abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 3 publications
(1 reference statement)
0
12
0
Order By: Relevance
“…However, the formerly passive Japanese patient seems to have undergone a transformation (1) (10) of the Japanese general population reported that patient beliefs about health might also be associated with autonomy preference. Previous studies (11,12) (13,14). The vignettes were limited to hypertension encounters to provide more reliable information about decisionmaking preferences.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the formerly passive Japanese patient seems to have undergone a transformation (1) (10) of the Japanese general population reported that patient beliefs about health might also be associated with autonomy preference. Previous studies (11,12) (13,14). The vignettes were limited to hypertension encounters to provide more reliable information about decisionmaking preferences.…”
Section: Introductionmentioning
confidence: 94%
“…De c i s i o n Ma k i n g P r e f e r e n c e a n d T h e i r De t e r mi n a n t s ( n = 9 2 ) physicians, and our results seemed to partially prove the hypothesis: preferences for decision-making decreased when physician age increased (P<0.05), and when patients preferred man physicians to woman physicians (NS), and preferences for information-seeking decreased when patients preferred man physicians to woman physicians (P<0.01). Alternatively, there are two studies (20,21) (8,12,14) …”
Section: Subjects and Samplingmentioning
confidence: 99%
“…1 Previous studies have been performed largely in the elective procedure environment and have suggested that recall of risk information is poor. [2][3][4][5][6] There is some literature to support improved recall and retention when adjunctive processes such as audiovisual aids are used, however these results have been variable. 5,[7][8][9][10] In this study we sought to determine if patients who receive written or audiovisual information prior to coronary angiography, comprehend and recall more information than when the information is offered in the standard manner, which involves the delivery of verbal information by clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…(18,19) Studies have shown that patients are different in terms of the amount of information they want and are able to understand and remember. (4,7,20,21) Some patients may not want to know such details. (22) This study showed that most surgeons agreed that the informed consent is better to be done by the doctor himself who is going to operate the patient because he can provide all necessary information to the patient.…”
Section: Discussionmentioning
confidence: 99%